Circular multi-directional patch antenna array with selectable beams using a novel feed structure and equilateral triangular patches - Konca, Mustafa; Uysal, Sener (My University, 2010)
A novel circular feed network is designed and utilized to feed an array of six equilateral triangular patches. The circular array can radiate in eight different directions depending on which of the four input ports are excited. The proposed feed network is considerably smaller compared to other networks with similar functions. Additionally it can steer beams in two dimensions, covering a wide area within the upper hemisphere rather than steering in only one plane. The antenna is designed for use in 2.45 GHz ISM band and utilizes a suspended FR4 substrate. The antenna array is only composed of passive microstrip elements which reside on the same layer, making it easy to manufacture. © 2010 IEEE.
2010 10th Mediterranean Microwave Symposium, MMS 2010 --
Keywords: Circular array; Circular divider; Circular feed network; Equilateral triangular patch; Multi-beam antenna; Multidirectional antenna; Passive phased array